Improved reconstruction of highly boosted τ-lepton pairs in the ττ → (μνμ ντ )(hadrons + ντ) decays channels with the ATLAS detector - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Rassloff, Damir Fabrice; Sanfilippo, Lorenzo; Schöning, André; et al. (The European physical journal. C, Particles and fields, 2025)
This paper presents a new $$τ $$-lepton reconstruction and identification procedure at the ATLAS detector at the Large Hadron Collider, which leads to significantly improved performance in the case of physics processes where a highly boosted pair of $$τ $$-leptons is produced and one $$τ $$-lepton decays into a muon and two neutrinos ($$τ _μ $$), and the other decays into hadrons and one neutrino ($$τ _had$$). By removing the muon information from the signals used for reconstruction and identification of the $$τ _had$$candidate in the boosted pair, the efficiency is raised to the level expected for an isolated $$τ _had$$. The new procedure is validated by selecting a sample of highly boosted $$Z→ τ _μ τ _had$$candidates from the data sample of 140 $$fb^{-1}$$of proton-proton collisions at 13 TeV recorded with the ATLAS detector. Good agreement is found between data and simulation predictions in both the $$Z→ τ _μ τ _had$$signal region and in a background validation region. The results presented in this paper demonstrate the effectiveness of the $$τ _had$$reconstruction with muon removal in enhancing the signal sensitivity of the boosted $$τ _μ τ _had$$channel at the ATLAS detector.
Online veröffentlicht: 27. Juni 2025
*ATLAS Collaboration: G. Aad, A. Ackermann, L.M. Baltes, F. Bartels, S. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, T. Mkrtchyan, D.F. Rassloff, L. Sanfilippo, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, L. Vigani, M. Wessels, J. Zinsser [und sehr viele weitere Personen]
Gesehen am 08.01.2026
Im Titel ist das zweite μ sowie das vierte und fünfte τ tiefgestellt